Characterization of late antique and early medieval pottery production of the city of Braga and its territory - Peñin, Raquel Martínez (2016)
The fundamental goal we set ourselves when developing this study is to try to characterize, both technically and formally, ceramics made in the city of Braga and its territory from the initial moments of the Late Antiquity to the Middle Ages. Thus, we will focus on analyzing some own productions that appear attached to the phases of late antique occupation —ceramics of red engobes and late gray—, as well as in the early medieval containers identified in different archaeological interventions practiced in the Braga environment. Concretely, we will analyze the material from various excavations conducted recently at the Theatre in the solar number 20/28 and 36/56 from the Afonso Henriques Street and the former District Hostel as well as the church of São Martinho de Dume.